Optimization of Drilling Bit Performance: A Cost-Per-Foot and Breakeven Analysis of Well-A and Well-B at Pan Ocean Oil Corporation Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
The assessment of drilling bit performance is essential for maximizing drilling process operational effectiveness and cost-efficiency. Using cost per foot and breakeven analysis, this study evaluates drilling bit performance to identify the best bit for fully drilling a well while lowering expenses. Well-A and Well-B of Pan Ocean Oil Corporation Nigeria were the subject of a case study that examined the effectiveness of seven distinct bits that were used to drill each well. With a breakeven rate of 51.51 feet per hour and the best cost per foot performance of $113.45/ft on run 1, Well-A reached a total depth of 13,203 feet. The best performance was shown by the 16"Baker MX-D53DX bit in run 2 in Well-B, which reached a depth of 13,866 feet. It cost $79.88/ft and broke even at78.14 ft/hr. Internet searches, case studies, and online resources were used to collect data. Bit optimization, specifically with the Baker T13 and BakerMX-D53DX, provided significant cost savings and increased penetration rates, according to the results. The significance of choosing an economical bit to maximize drilling efficiency and lower operating costs is emphasized by this study.